Pengaruh Gerakan Yoga Child's And Animals Poses Terhadap Perubahan Skala Nyeri Dismenore Pada Mahasiswi - Ulfa Tri Oksianti Widiastuti; Ragil Setiyabudi (Jurnal Keperawatan Muhammadiyah, 2020)
Abstrak Background: Dysmenorrhea is menstruation accompanied by pain and physical causes such as nausea, vomiting, diarrhea and in some cases it can also disrupt daily activity. Students who experience dysmenorrhea will be disrupted during learning activities because it is an activity that involves both physical work and the brain. Furthermore, it is found recently that the pain during menstruation is not only felt in the lower abdomen, but it reaches the back. Objective: To determine the effect of the child and animal poses yoga on the changes of the pain scale in dysmenorrhea in students of the Faculty of Health Science, Universitas Muhammadiyah Purwokerto. Method: This study used a quasi-experimental design which was a non-equivalent control group pre-test-post test. Samples were collected by means of purposive sampling with a total of 80. Forty female students were given interventions of yoga child and animal poses and there were 40 control groups. In addition, a paired sample t-test was used in the statistical test. Results: There was a change of 1.62 in pain in the intervention group scale. On the other hand, there was a change in the pain scale of 0.06 in the control group. Statistical test results showed the value of p = 0.0001. Conclusion: The movement of yoga child and animal poses have an effect on the dysmenorrhea pain scale since it can decrease the pain caused by dysmenorrhea.Keywords :Child and animal poses yoga, Dysmenorrhea, Pain scale